Survival Analysis after Core Decompression in Association with Platelet-Rich Plasma, Mesenchymal Stem Cells, and Synthetic Bone Graft in Patients with Osteonecrosis of the Femoral Head - D'Ambrosi, Riccardo; Biancardi, Elena; Massari, Giulia; Ragone, Vincenza; Facchini, Renato Mario (Joints, 2018)
Purpose The aim of this study was to report the rate of survivorship in patients with osteonecrosis of the femoral head treated with core decompression in association with mesenchymal stem cells (MSCs) implantation, platelet-rich plasma (PRP) injection, and synthetic bone graft.Methods We evaluated 24 hips in 16 patients, according to Ficat classification, treated by core decompression, injection of PRP and MSCs, and backfilling of the core tract with synthetic bone graft. Survivorship was estimated using Kaplan–Meier curves.Results The survivorship of core decompression in association with the procedure is 50% at 75 months of follow-up. The survival rate was 80% for patients in early stage and 28.6% for patients in advanced stage at 75 months. When we compared Kaplan–Meier survival curves of patients in stage III + IV and patients in stage I + II, we noticed that the survival functions are statistically different (p < 0.05, log-rank test), particularly in stage I + II where we had a greater surviving core decompression, in comparison to patients in stage III + IV.Conclusion This technique is safe and good preliminary results were obtained in patients with early stages of the disease with no reported complications.Level of Evidence Level IV, therapeutic case series.
Keywords: femoral head osteonecrosis; core decompression; platelet-rich plasma; mesenchymal stem cells; synthetic bone graft